A Simple and Fast Electrochemical CO2 Sensor Based on Li7La3Zr2O12 for Environmental Monitoring. Issue 44 (20th September 2018) - Struzik, Michal; Garbayo, Inigo; Pfenninger, Reto; Rupp, Jennifer L. M.
Abstract: In the goal of a sustainable energy future, either the energy efficiency of renewable energy sources is increased, day‐to‐day energy consumption by smart electronic feedback loops is managed in a more efficient way, or contribution to atmospheric CO2 is reduced. By defining a next generation of fast‐response electrochemical CO2 sensors and materials, one can contribute to local monitoring of CO2 flows from industrial plants and processes, for energy management and building control or to track climate alterations. Electrochemical Li + ‐garnet‐based sensors with Li7 La3 Zr2 O12 solid electrolytes can reach notable 1 min response time at lowered operation temperatures to track 400–4000 ppm levels of CO2 when compared with state‐of‐the‐art NASICON‐based sensors. By using principles of redefining the electrode electrochemistry, it is demonstrated that Li6.75 La3 Zr1.75 Ta0.25 O12 can be used to alter its classic use as energy‐storage function to gain additional functions such as CO2 tracking. Abstract : Toward fast and energy efficient CO2 sensing, a potentiometric device based on a Li‐garnet solid electrolyte is demonstrated. Application of typical fast conducting solid‐state battery electrolyte known from batteries is redefined using nonstandard electrode materials changing its function from energy storage to CO2 environmental monitoring, resulting in fast response time <60 s at lower temperatures than state‐of‐the‐art devices.